2021
DOI: 10.1002/dvg.23422
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and function of super enhancer RNA

Abstract: Super enhancer (SE) is a cluster of enhancers that has a stronger ability to promote transcription compared to the typical enhancer (TE). Similar to TE, which can transcribe enhancer RNA (eRNA), SE produces super enhancer RNA (seRNA). The activation of SE is cell and tissue-specific, and the SE-associated genes are mostly linked to the cell fate. This is demonstrated by the important role-played by SE in the embryonic stem cell (ESC) and multiple cancer development. SeRNA regulates transcription in both cis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 69 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…elncRNAs perform regulatory transcriptional functions by -cis and -trans mechanisms ( 21 ). The roles of seRNAs include chromatin loops stabilization, and transcription factor recruitment among others, and thus seRNAs mediate various cellular activities in the cytoplasm ( 52 ). To further explore the molecular mechanism of LINC01485 involvement in osteogenic differentiation process, we first identified the subcellular localization of LINC01485 and found that LINC01485 is mainly localized in the cytoplasm, consistent with the results reported by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…elncRNAs perform regulatory transcriptional functions by -cis and -trans mechanisms ( 21 ). The roles of seRNAs include chromatin loops stabilization, and transcription factor recruitment among others, and thus seRNAs mediate various cellular activities in the cytoplasm ( 52 ). To further explore the molecular mechanism of LINC01485 involvement in osteogenic differentiation process, we first identified the subcellular localization of LINC01485 and found that LINC01485 is mainly localized in the cytoplasm, consistent with the results reported by Zhou et al.…”
Section: Discussionmentioning
confidence: 99%
“…Superenhancers (SE) are the type of cluster of merged enhancers located proximally in the genome, typically within 12.5 kb, and have unusually high levels of master TF, RNAPII, cofactors like the mediator and integrator complex and other enhancer-associated features, such as H3K27ac and H3K4me1. They are also associated with high transcription values of eRNA and associated target genes, but also with a higher frequency of chromatin interactions with respect to individual enhancers [55] , [56] , [57] , [58] , [59] , [60] , [61] . In addition, the enhancers that compose the SE ( constituent enhancers ) are usually linked to the same regulatory process.…”
Section: Methodsmentioning
confidence: 99%
“…DNA and RNA involved in triplex are present in transcription start sites and enriched with active epigenetic marks H3K4 methyl. Surprisingly, the RNA part but not the DNA of DNA:RNA triplexes are enriched at super-enhancer, which are transcribed bidirectionally into ncRNAs ( Xiao et al, 2021 ), suggesting that this RNA transcribed from enhancer can form triplexes in trans . Hence, it was proposed that these ncRNAs produced at enhancers might contact distal regions via the formation of DNA:RNA triplexes and induce transcription ( Sentürk Cetin et al, 2019 ).…”
Section: Non-canonical Rna Structures In Organism Developmentmentioning
confidence: 99%